DYNAMIC ALGORITHM FOR DIMENSIONAL SUB-TUNING IN TURNING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
One of the possibilities for increasing the accuracy when machining a series of parts with a single dimensional adjustment (automatic obtaining of dimensions) is to perform more frequent dimensional sub-tuning. There is a possibility to increase the accuracy of machining through dimensional sub-tuning if working with a complete set of data about the dimensions of the machined parts, and not with small current samples. This opportunity arises from the widespread introduction of computer technology for the purposes of managing the technological processes. The article examines the possibilities for determining the moment for dimensional sub-tuning by using computer analysis of information about the dimensions of the machined parts in real time.